Evaluation of Additional Emergency Brake Button Installation to Reduce Risk Priority Number (RPN) for Main Emergency Brake Failure in a 350 HP Drawworks Rig - Rozi Mexiwel; Benidiktus Tulung Prayoga; Lilik Dwi Setyana (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Emergency brake failure in a 350 HP drawwork rig poses significant operational and safety risks due to single-point-of-failure conditions within the braking system. Objective: This study aimed to evaluate the effectiveness of installing a secondary emergency brake system in reducing the Risk Priority Number (RPN) and mitigating the risk of primary emergency brake failure. Method: A quantitative evaluative approach was employed using integrated Failure Mode and Effects Analysis (FMEA) and Fault Tree Analysis (FTA), with data collected from maintenance records, inspection reports, failure records, and incident reports over a 12-month operational period. Results and Discussion: The results showed that the implementation of the secondary emergency brake significantly reduced RPN values by 55.6%-63.4% and decreased system failure probability by 63.8%73.3%, while improving system reliability, emergency response capability, and operational safety through the elimination of single-point-of-failure conditions using a dual pilot valve configuration. The integration of FMEA and FTA enabled a comprehensive assessment of critical failure modes, causal relationships, and risk mitigation priorities. Conclusions: The installation of a secondary emergency brake system is an effective risk mitigation strategy that enhances the safety, reliability, and operational performance of 350 HP drawwork rigs while providing a comprehensive framework for evaluating critical safety systems in drilling operations.